2019
DOI: 10.5530/ijmedph.2019.3.16
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Pathogen Profile and Knowledge, Attitude and Behavior about Food Hygiene among Food Handlers in a Tertiary Health Care Center

Abstract: Introduction: The highest estimated cause of death in South East Asian Region (SEAR) attributes to diarrheal diseases (Global Food Infection Network, 2011). According to the CDC, 20 to 40% of foods borne illness associated with the consumption of contaminated food were from catering establishments. The purpose of the study was to assess the enteric pathogen profile and knowledge, attitude and behaviour regarding food hygiene among food handlers in our tertiary care center. Methods: Food handlers (n=123) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…Regarding the prevalence of antimicrobial resistance phenotypes, 13.6% of C. jejuni isolates demonstrated multidrug resistance to 3 or more different classes of antimicrobials, and 57.6% of C. jejuni isolates were resistant to at least one antimicrobial tested. The number of MDR C. jejuni isolates reported in this study was higher than the result (<3%) previously reported by NARMS integrated report and the results (3.5%) reported by Mathew et al ( 48 , 49 ), which may indicate that antibiotic resistance is spreading or increasing among the Campylobacter in poultry. However, in a survey conducted in human patients, C. jejuni isolates showed much higher MDR 56.8% ( 50 ).…”
Section: Discussioncontrasting
confidence: 80%
“…Regarding the prevalence of antimicrobial resistance phenotypes, 13.6% of C. jejuni isolates demonstrated multidrug resistance to 3 or more different classes of antimicrobials, and 57.6% of C. jejuni isolates were resistant to at least one antimicrobial tested. The number of MDR C. jejuni isolates reported in this study was higher than the result (<3%) previously reported by NARMS integrated report and the results (3.5%) reported by Mathew et al ( 48 , 49 ), which may indicate that antibiotic resistance is spreading or increasing among the Campylobacter in poultry. However, in a survey conducted in human patients, C. jejuni isolates showed much higher MDR 56.8% ( 50 ).…”
Section: Discussioncontrasting
confidence: 80%
“…8 9 Moreover, according to the Centers for Disease Control and Prevention, as cited in Mathew et al, 10 20%-40% of foodborne illnesses associated with consumption of contaminated food originated from catering establishments. 10 Food handling personnel play a role in the transmission of foodborne diseases. The health of food handlers is of great importance in maintaining the quality of food products.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The report also estimated that infected food workers were documented as responsible for 18% of 766 outbreaks occurring in the USA 8 9. Moreover, according to the Centers for Disease Control and Prevention, as cited in Mathew et al ,10 20%–40% of foodborne illnesses associated with consumption of contaminated food originated from catering establishments 10…”
Section: Introductionmentioning
confidence: 99%
“…According to the Centers for Disease Control (CDC), as cited in Mathew RR (2019), 20 to 40% of food borne illness associated with the consumption of contaminated food originated in catering establishments [1]. According to the World Health Organization (WHO; 2015), foodborne diseases are an important cause of morbidity and mortality, and a significant impediment to socioeconomic development globally [2].…”
Section: Introductionmentioning
confidence: 99%
“…al (2012) found that the parasites Ascaris lumbricoides, Entamoeba histolytica, and Giardia lamblia were observed in certified food-handlers [11]. Ranl Rose Mathew et al (2019), in a study of 123 study participants in India, found a prevalence of enteric pathogens of 5.2%, in which four stool specimens were positive for intestinal parasites (two-Giardia intestinalis, one-Entamoeba histolytica, one-Blastocystis hominis) and Campylobacter jejuni was isolated from stool samples of two food handlers [12] From a total of 212 microbiological samples, Metin Erdogan and Şebnem Pamuk (2019) found that most isolates were harvested from hands (52%) and food samples (36%), whereas few isolates (12%) were obtained from kitchen equipment [13]. Ncube, F. et al (2020) found that data from field observations indicated that contrary to self-reported information, a substantial proportion of food handlers did not use a detergent or disinfectant to wash their hands before food handling or posthandling potentially contaminated materials [14].…”
Section: Introductionmentioning
confidence: 99%